Uictorem uictae subcubuisse queror: representaciones del pudor masculino en las Heroidas 4, 9 y 17 de Ovidio (Argos, 2024)
In this paper, we analyze Heroides 4, 9 and 17 in which Phaedra, Deianira and Helen question the pudicitia of their male counterparts: Hippolytus, Hercules and Paris, respectively. We consider the heroes’ characteristics and the fictional writing context of each letter to delimit the scope of masculine sexual morality. Our reading hypothesis proposes that the heroines write with the intention of confronting the tradition, which considers them impudent, and so they elaborate the epistolary discourse in order to present their behavior as appropriate and the masculine behavior as inadequate.
Keywords: Pudicitia; pudor; sexual morality; masculinity; feminine voice